Incidence of intimate partner violence among Ugandan women with pelvic floor dysfunction. Issue 3 (11th January 2019) - Krause, Hannah; Ng, Shu‐Kay; Singasi, Isaac; Kabugho, Emma; Natukunda, Harriet; Goh, Judith
Abstract: Objective: To assess the occurrence of intimate partner violence (IPV) among women seeking surgery for pelvic floor dysfunction (PFD) in a rural African community. Methods: A prospective questionnaire‐based study was conducted among women with obstetric fistula, unrepaired obstetric anal sphincter injuries (OASIS), or severe (stage 3 or 4) pelvic organ prolapse (POP) who attended surgical camps at Kagando Hospital in western Uganda between July 15, 2016, and September 14, 2017. The control group comprised women without PFD. Participants completed the Hurt, Insult, Threaten, and Scream (HITS) tool and the Woman Abuse Screening Tool (WAST) to screen for IPV. Results: 117 of the 312 women interviewed reported current IPV: 73/214 (34.1%) in the PFD group and 44/98 (44.9%) in the control group. The PFD group comprised unrepaired OASIS (n=85, 39.7%), obstetric fistula (n=75, 35.1%), and severe POP (n=54, 25.2%). All groups experienced high levels of IPV. The frequency of positive screening results for IPV with WAST (score ≥13.0) and/or HITS (score ≥10.5) were: severe POP (n=17, 31.5%), obstetric fistula (n=28, 37.3%), unrepaired OASIS (n=30, 35.3%), and control group (n=44, 44.9%). Conclusion: Women in western Uganda experienced high rates of IPV, regardless of whether or not they had PFD. ANZCTR number: ACTRN12617001073392. Abstract : Women living in western Uganda experienced extremely high rates of intimate partner violence, regardless of whether or not they had pelvic floor dysfunction.